Everyone Likes to Be Liked: Experimental Evidence from Matching Markets - Timm Opitz; Christoph Schwaiger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Matching markets can be unstable when individuals prefer to be matched to a partner who also wants to be matched with them. Through a pre-registered and theory-guided laboratory experiment, we provide evidence that such reciprocal preferences exist, significantly decrease stability in matching markets, and are driven both by belief-based and preference-based motives. Participants expect partners who want to be matched with them to be more cooperative, and are more altruistic themselves. This leads to higher cooperation and larger profits when participants can consider each other's preferences.
Keywords: C78; C91; C92; D82; D83; D91; 330; experiment; market design; matching; reciprocal preferences; incomplete information; Gale-Shapley deferred acceptance mechanism